Can you hear the sea? - Cumberbatch, Judy (Bloomsbury : Distributed to the trade by Holtzbrinck Publishers, 2006)
Sarah's grandpa gives her a special shell and says if she listens carefully she can hear the sea, but all she hears are everyday village noises.